2018
DOI: 10.1186/s12882-018-1059-2
|View full text |Cite
|
Sign up to set email alerts
|

Home hemodialysis treatment and outcomes: retrospective analysis of the Knowledge to Improve Home Dialysis Network in Europe (KIHDNEy) cohort

Abstract: BackgroundUtilization of home hemodialysis (HHD) is low in Europe. The Knowledge to Improve Home Dialysis Network in Europe (KIHDNEy) is a multi-center study of HHD patients who have used a transportable hemodialysis machine that employs a low volume of lactate-buffered, ultrapure dialysate per session. In this retrospective cohort analysis, we describe patient factors, HHD prescription factors, and biochemistry and medication use during the first 6 months of HHD and rates of clinical outcomes thereafter.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 34 publications
1
28
0
17
Order By: Relevance
“…Moreover, overall survival in our cohort was high -80% at 5 years and was consistent with survival seen in other cohorts of extended or more frequent dialysis. 3,4,21,22 This suggests that our cohort was representative of patients typically offered more intensive dialysis schedules, who are known to have better prognostic characteristics than those performing standard hours. 2,6,11 Cohort studies utilize a variety of matching methodologies to account for the difference in the characteristics of people practising more intensive dialysis schedules when assessing the impact of these schedules and obtain wide variation in estimates of the survival benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, overall survival in our cohort was high -80% at 5 years and was consistent with survival seen in other cohorts of extended or more frequent dialysis. 3,4,21,22 This suggests that our cohort was representative of patients typically offered more intensive dialysis schedules, who are known to have better prognostic characteristics than those performing standard hours. 2,6,11 Cohort studies utilize a variety of matching methodologies to account for the difference in the characteristics of people practising more intensive dialysis schedules when assessing the impact of these schedules and obtain wide variation in estimates of the survival benefit.…”
Section: Discussionmentioning
confidence: 99%
“…14 The low persistence with extended hours dialysis in this cohort is in contrast with observational studies that report 68% to 85% of those performing frequent or extended haemodialysis will continue with that modality over follow-up periods between 18 months and 5 years. 3,22,26 These studies were entirely or predominantly homebased and there is little data assessing persistence with in-centre intensive haemodialysis. The only other randomized evidence comes from the FHN Nocturnal study, which reported adherence to frequent long nocturnal dialysis (totalling more than 27 h/wk) of over 50% during the follow-up period among those randomized to this schedule (as opposed to approximately 30% cross-over in the standard arm).…”
Section: Discussionmentioning
confidence: 99%
“…10 000 weltweit behandelten Patienten am meisten Daten vor. In retrospektiven Analysen konnte gezeigt werden, dass mit diesem System eine sehr gute chronische Dialysequalität erreicht werden kann, die der konventionellen Zentrumsdialyse nicht unterlegen ist [9,13]. Hieraus ergibt sich allerdings auch eine Herausforderung für die deutsche Nephrologie, da es sich abzeichnet, dass die Verbrauchsmaterialien aufgrund der komplexen Kassettensysteme und der höheren Behandlungsfrequenz wohl kostenaufwendiger sein werden, als dies beim herkömmlichen Dialyseregime der Fall ist.…”
Section: Neue Möglichkeiten Der Hhdunclassified
“…Eine solche Regelung wäre für die HHD auch deshalb sinnvoll, weil alle detaillierteren Berechnungen von einer gesellschaftsökonomischen Kostenreduktion durch die HHD ausgehen. Diese hängt v. a. mit dem Wegfall der Fahrtkosten, niedrigerer Hospitalisierungsfrequenz und geringerem Pflegeaufwand zusammen [13,14].…”
Section: Neue Möglichkeiten Der Hhdunclassified
See 1 more Smart Citation